Philippine structural transformation in the context of technological change - Leonardo A. Lanzona (Philippine Institute for Development Studies (PIDS), 2022)
One aspiration of the Agricultural Fisheries Modernization Act (AFMA) is the promotion of industry dispersal and rural industrialization. This involves a policy of structural transformation, which attempts to transition the economy from a low productivity sector, such as agriculture, to a high productivity sector, such as industry. This study shows that despite the efforts of AFMA, this process has not been accomplished. Previous literature has attributed this failure to many factors, including policy failure and lack of investments. However, the paper argues that the role of technological change has not been given considerable attention. Empirical analysis demonstrates that policy formulation and capital accumulation are not sufficient in achieving structural transformation. Even if the correct policies are implemented and adequate investments are available, the sustainable transition from agriculture to industrialization will require the adoption of appropriate technology that utilizes local resources, including labor. To do this, the government must set up not only an environment for research and development and extension but also provide incentives in the form of transfers to the private sector to invest in technology.
Keywords: 330; Structural Transformation; Technology Transfer; Urbanization; Knowledge Spillover; Employment